1998
DOI: 10.1128/mcb.18.2.846
|View full text |Cite
|
Sign up to set email alerts
|

The AML1-MTG8 Leukemic Fusion Protein Forms a Complex with a Novel Member of the MTG8(ETO/CDR) Family, MTGR1

Abstract: The AML1-CBF␤ transcription factor complex is essential for the definitive hematopoiesis of all lineages and is the most frequent target of chromosomal rearrangements in human leukemia. In the t(8;21) translocation associated with acute myeloid leukemia (AML), the AML1(CBFA2/PEBP2␣B) gene is juxtaposed to the MTG8(ETO/CDR) gene. We show here that the resultant AML1-MTG8 gene product specifically and strongly interacts with an 85-kDa phosphoprotein. Molecular cloning of cDNA indicated that the AML1-MTG8-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
158
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(168 citation statements)
references
References 60 publications
10
158
0
Order By: Relevance
“…The complex marked with the arrowhead was supershifted such that it was unable to enter the gel when extracts were preincubated with polyclonal antibody to Tal1 (anti-Tal1) or a monoclonal antibody to p300 (RW128) (anti-p300) but not with a monoclonal antibody to a human c-Myc epitope (9E10) (anti-Myc epitope) or Tal1 preimmune immunoglobulin (Tal1 preimmune) p300 and TAL1 transcriptional activity S Huang et al 1998). While modest from a quantitative standpoint, the magnitude of p300-stimulated coactivation was comparable to that described for BETA-2 (Mutoh et al, 1998), Smad3 (Janknecht et al, 1998), and AML1 (Kitabayashi et al, 1998). Finally, no e ect of p300 was seen in cells transfected with the reporter plasmid alone (Figure 4).…”
Section: P300 Augments Transcription Stimulated By Tal1-e12 Heterodimerssupporting
confidence: 66%
“…The complex marked with the arrowhead was supershifted such that it was unable to enter the gel when extracts were preincubated with polyclonal antibody to Tal1 (anti-Tal1) or a monoclonal antibody to p300 (RW128) (anti-p300) but not with a monoclonal antibody to a human c-Myc epitope (9E10) (anti-Myc epitope) or Tal1 preimmune immunoglobulin (Tal1 preimmune) p300 and TAL1 transcriptional activity S Huang et al 1998). While modest from a quantitative standpoint, the magnitude of p300-stimulated coactivation was comparable to that described for BETA-2 (Mutoh et al, 1998), Smad3 (Janknecht et al, 1998), and AML1 (Kitabayashi et al, 1998). Finally, no e ect of p300 was seen in cells transfected with the reporter plasmid alone (Figure 4).…”
Section: P300 Augments Transcription Stimulated By Tal1-e12 Heterodimerssupporting
confidence: 66%
“…A/E-D401, which lacks the C-terminal zinc ®nger domain and one proline-serine/threonine rich region, retains transforming potential, whereas A/E-D292 does not. Previous studies have shown that a mutant similar to A/E-D401 can repress TCRb enhancer activity, but that the A/E-D292 mutant does not repress transcription Kitabayashi et al, 1998). Neither of these mutants can upregulate BCL-2 promoter activity (Klampfer et al, 1996), suggesting that transforming activity correlates best with the ability of AML1/ETO to repress transcription of AML1B activated promoters.…”
Section: Discussionmentioning
confidence: 97%
“…Neither of these mutants can upregulate BCL-2 promoter activity (Klampfer et al, 1996), suggesting that transforming activity correlates best with the ability of AML1/ETO to repress transcription of AML1B activated promoters. A recent mutational analysis of AML1/ETO identi®ed the 292 ± 401 aa region as being essential for the ability of AML1/ETO to block the differentiation and G-CSF dependent proliferation of L-G murine myeloid progenitor cells and to interact with the MTGR1 protein (Kitabayashi et al, 1998). Thus, studies of AML1/ETO in numerous cell types demonstrate the importance of the 292 ± 401 a.a. region of AML1/ETO to its biological functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations